To tube or not to tube: a skeptic's guide to nonintubated thoracic surgery. Issue 1 (10th February 2021) - Schieren, Mark; Defosse, Jerome
Abstract : Purpose of review: The aim of this review is to provide an overview of the rationale and evidence for nonintubated thoracic surgery and guide clinicians, considering the implementation of nonintubated thoracic surgery, to find an anesthetic approach suitable for their department. Recent findings: Based on physiologic considerations alone, nonintubated thoracic surgery would be expected to be an advantageous concept in thoracic anesthesia, especially in patients at high risk for pulmonary complications. Currently existing evidence, however, does not support these claims. Although the feasibility and safety have been repeatedly demonstrated, high-quality evidence showing a significant benefit regarding clinically relevant patient-centered outcomes is not available. Anesthetic approaches to nonintubated thoracic surgery differ significantly; however, they usually concentrate on six main aspects: maintenance of airway patency, respiratory support, analgesia, patient comfort, cough suppression, and conversion techniques. Given the lack of high-quality studies comparing different techniques, evidence-based guidance of clinical decision-making is currently not possible. Until further evidence is available, anesthetic management will depend mostly on local availability and expertise. Summary: In select patients and with experienced teams, nonintubated thoracic surgery can be a suitable alternative to intubated thoracic surgery. Until more evidence is available, however, a general change in anesthetic management in thoracic surgery is not justified.